Analysis of a support method for offering delivery promises in environments managed by S-DBR system - Filho, Isidoro Rays [UNESP]; de Souza, Fernando Bernardi [UNESP]; Ikeziri, Lucas Martins [UNESP] (FapUNIFESP (SciELO), 2023)
Paper aims: The objective of this paper is to investigate the effectiveness of a method, here denominated the due date promise by slack time rule (DDPSTR), to evaluate its feasibility and effectiveness for accepting urgent orders in make-to-order (MTO) environments managed by the Simplified Drum-Buffer-Rope (S-DBR) system. Originality: Evaluating alternative methods for dealing with urgent orders in MTO environments managed and controlled by the S-DBR system is a subject that has received little attention from academia. This study contributes to the field of knowledge by identifying and comparing three alternatives. Research method: To evaluate its feasibility and effectiveness, the DDPSTR was compared with variations of a method based on prior reserve capacity when dealing with regular and urgent orders. Computer simulation was used to model a theoretical production line that emulated the S-DBR system in different scenarios, using average delay and percentage of late orders as performance indicators. Main findings: The DDPSTR method achieved optimal results for both indicators, enabling reliable delivery dates and, at the same time, flexibility in accepting urgent orders. Implications for theory and practice: This work has verified the effectiveness of the DDPSTR method as a means of dealing with urgent orders without compromising the reliability of previously promised order deadlines. It has additionally proposed the means by which future research can evaluate adaptations, such as offering the shortest feasible delivery times to customers when those initially requested by them prove unworkable.
Keywords: Make to order; Production planning and control; Simulation; Theory of Constraints